(3aGYdjI GdCdYGH GdJYdjejI ai JfejI HYV GdegGQGJ GdMjGJjI dOi GdJdGejP GdeYGbjf YbdjG GdbGHdjf ddJYdje (B/ s - (3SGei SYO YHOGdbGOQ eMehOs; (3CSeGA Jhajb eHQhc (B: s; (3efi MSf GdSjO (B: s ((3GdbGgQI (B: s (3SGei SYO YHOGdbGOQ eMehO (B: s, 2010)
(3JYO GdEYGbI GdYbdjI ef GdeTcdGJ GdNWjQI GdJj jecf Cf JhGLg GdaQO(B: (3h GdJj jecf Cf jJeKd CKQgG GdeHGTQ aj JOfj eSFhdjI COGFg GdhXjai GdYbdj h Pdc Edj GdOQLI GdJj JLYdg jJeKd hLgG CSGSjG ef ChLg GdbUhQ GdYOjOI GdJj jYGfj efgG Pdc GdaQO MjK Cf GdLGfH GdYbdj QZe eG jYGfjg eKd gPG GdaQO ef eTcdGJ eJYOOI jYO gh CUd GdEYGbI GdJj jYGfj efgG(B: (3hGdJj JJQJH YdjgG eTcdGJ LeI aj GdYOjO ef LhGfH Gdfeh GdCNQi(B: (3haj ZjQgG ef GdegGQGJ GdeNJdaI GdJj JYJHQ VQhQjI cj jJecf GdWad ef GdYjT Ch GdJYGjT eY GdBNQjfs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ hGdHMhK GdJQHhjI (B- (3bSe GdEQTGO GdfaSi h GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCdYGH GdJYdjejI s; (3GdJdGejP GdeYGbjf YbdjG s; (3GdegGQGJ GdMjGJjI s